2008
DOI: 10.1002/mds.22430
|View full text |Cite
|
Sign up to set email alerts
|

Progression of dysprosody in Parkinson's disease over time—A longitudinal study

Abstract: Parkinsonian speech or hypokinetic dysarthria results from a multidimensional impairment of phonation, articulation, and prosody. Although the dysprosody in Parkinson's disease (PD) is well described (alterations in speech rate and pause time, speech intensity and pitch variation), little is known about alterations of these single prosodic parameters over a longer time course. The objective of this study is to analyze changes of speech rate and pitch variation in patients with PD over time and to compare these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
114
1
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 183 publications
(128 citation statements)
references
References 30 publications
5
114
1
8
Order By: Relevance
“…Adjustment to the Portuguese and application to patients with Parkinson's disease of protocol within central origin dysarthrias' assessment Angélica Suelen Fracassi (1) , Ana Rita Gatto (2) , Silke Weber (3) , André Augusto Spadotto (4) , Priscila Watson Ribeiro (5) , Arthur Oscar Schelp (6) RESUMO Objetivo: traduzir e adaptar protocolo desenvolvido por pesquisadores alemães, adequando-o às características fonéticas e linguísticas do português falado no Brasil. Caracterizar os componentes de fala mais alterados na população com doença de Parkinson, comparando-os com grupo de sujeitos normais na mesma faixa etária.…”
Section: Adaptação Para a Língua Portuguesa E Aplicação De Protocolo unclassified
“…Adjustment to the Portuguese and application to patients with Parkinson's disease of protocol within central origin dysarthrias' assessment Angélica Suelen Fracassi (1) , Ana Rita Gatto (2) , Silke Weber (3) , André Augusto Spadotto (4) , Priscila Watson Ribeiro (5) , Arthur Oscar Schelp (6) RESUMO Objetivo: traduzir e adaptar protocolo desenvolvido por pesquisadores alemães, adequando-o às características fonéticas e linguísticas do português falado no Brasil. Caracterizar os componentes de fala mais alterados na população com doença de Parkinson, comparando-os com grupo de sujeitos normais na mesma faixa etária.…”
Section: Adaptação Para a Língua Portuguesa E Aplicação De Protocolo unclassified
“…Movement symptoms in this progressive, neurodegenerative disorder can be managed with medication [5], however symptoms not controlled by medication, such as low mood and voice problems, may have a more negative effect on quality of life (QOL) with PD [6]. Ninety per cent of people with PD develop hypokinetic dysarthria [7], resulting in weakened respiration, short rushes of speech, reduced loudness, voice tremor, altered voice quality, imprecise articulation, and reduced pitch inflection (dysprosody) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that people with Parkinson (PWP) produce fewer words, take frequent pauses, and have abnormal speech rate [36]. These variations in voice patterns become worse as the disease progresses [35]. Research has shown that speech may be a useful signal for discriminating PWP from healthy individuals [37].…”
Section: Vocal Impairment In People With Parkinson's (Pwp)mentioning
confidence: 99%